ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENGENDALIAN INTERNAL PADA PT. JAYA MAKMUR ABADI - Maharani Intining Tyas; M. Sodik; Dwi Anggarani (Journal of Innovation Research and Knowledge, 2023)
The purpose of this research is to identify PR. Internal control and sales accounting information system Jaya Makmur Abadi. Qualitative descriptive research that uses qualitative data and is described descriptively is the research methodology used in this study. homework As a research subject, Jaya Makmur Abadi. Primary information is taken from PR documents. Jaya Makmur Abadi. Direct observation and conversations with the people involved were also carried out. The findings of this investigation suggest that the homework has caused the related functions to deviate from theory. The shipping feature is not used by Jaya Makmur Abadi. The concurrent work that the warehouse functions did emerge as a result of this. The procedures for cash and credit sales have not been carried out well enough, there are still procedures that have not been carried out.